Character development patterns through islamic religious education: a study at muhammadiyah 08 plus elementary school, jakarta - Murniati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This research is motivated by the importance of character development in students from elementary school age, particularly through Islamic Religious Education (PAI) learning, which plays a strategic role in instilling religious values and noble morals. The phenomenon of moral decadence among school-age children encourages the need for character development patterns integrated into the curriculum, school culture, and Islamic extracurricular activities. This study aims to analyze student character development through PAI, the character values fostered, and the supporting and inhibiting factors in the implementation of character development at Elementary School Muhammadiyah 08 Plus Jakarta. The research method used was a qualitative case study approach. Data were collected through interviews, observation, and documentation. Data were then analyzed through data reduction, data presentation, and conclusion drawing with validity tests using source and technique triangulation. This study found that character development through Islamic Religious Education (PAI) at Muhammadiyah 08 Plus Elementary School, Jakarta, is implemented in an integrated manner through intracurricular, cocurricular, and extracurricular activities, emphasizing the habit of worship, teacher role models, and the integration of character values into every lesson. The core values fostered are religiosity, honesty, discipline, and responsibility, reinforced by Muhammadiyah's distinctive values, such as JUARA (Honest, Excellent, Active, Religious, and Trustworthy). Supporting factors for successful character development include principal support, teacher competence, Islamic school culture, and the ISMUBA curriculum. Obstacles faced include time constraints, differences in student backgrounds, lack of synergy with parents, and negative influences from the outside environment. In conclusion, the pattern of character development through Islamic Religious Education (PAI) at Muhammadiyah 08 Plus Elementary School, Jakarta, has been implemented to instill noble morals and shape the personalities of students who are religious, disciplined, honest, and responsible. However, optimization is still needed, especially in strengthening collaboration with parents and consistent implementation of habits outside of school.